Complete genome sequence of the novel psychrobacter sp strain AJ006, which has the potential for biomineralization - Lee, Jun Ho; Lee, Pyung Cheon (Microbiology Resource Announcements, 2020)
A novel Psychrobacter sp. strain, AJ006, was isolated from Antarctic soil. Its complete genome sequence consists of a single circular chromosome (3,032,533 bp; G+C content, 44.0%) and a single linear plasmid (49,070 bp; G+C content, 41.7%). Chromosomal genes encoding carbonic anhydrase and urease, key enzymes in a biomineralization process, were predicted.